PENGARUH PENAMBAHAN TERUNG BELANDA (Solanum betaceum Cav.) TERHADAP KARAKTERISTIK MARSHMALLOW - Anita Devi, Ni Putu; Ari Sandhi W, Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 7 No 1 (2018): Jurnal ITEPA, 2018)
The aim of this research is to know the effect of the addition of tamarillo (Solanum betaceum Cav) to marshmallow characteristic, and to determine the addition of the best tamarillo to produce the best characteristic marshmallow. The experimental design used was Completely Randomized Design (RAL) by treatment with fruit pulp tamarillo as follows: 30 %, 40 %, 50 %, 60 %, 70 % and 80 %. Each treatment was repeated three times to obtain 18 experimental units. The results showed that the addition of tamarillo showed significant effect on water content, ash content, total anthocyanin, vitamin C, total sugar, elasticity, color score test, taste score test, texture score test, aroma and overall acceptance and no significant effect on color hedonic test and taste hedonic test. The best characteristic of marshmallow was obtained from the addition of tamarillo of 30 g with water content of 19.44%, ash content of 0.08%, total anthocyanin 0.44 mg / L, vitamin C 8.20 mg / 100g, total sugar 75.15%, elasticity of 1.47 N, color (rather pink and rather like), aroma (rather like), texture (very chewy and like), taste (sweet and rather like), overall acceptance (like).